2006
DOI: 10.1128/aem.03076-05
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Life Cycle of the Soil Saprophyte Bacillus cereus in Liquid Soil Extract and in Soil

Abstract: Bacillus is commonly isolated from soils, with organisms of Bacillus cereus sensu lato being prevalent. Knowledge of the ecology of B. cereus and other Bacillus species in soil is far from complete. While the older literature favors a model of growth on soil-associated organic matter, the current paradigm is that B. cereus sensu lato germinates and grows in association with animals or plants, resulting in either symbiotic or pathogenic interactions. An in terra approach to study soil-associated bacteria is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
1
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 32 publications
2
127
1
11
Order By: Relevance
“…B. cereus is mesophilic, and is capable of adapting to wide and varying environmental conditions, widely distributed in nature and commonly found in nature as a saprophyte. It grows optimally at temperatures between 20 and 40 Vilain et al, 2006 . Since it is a soil bacterium, it can easily enter different food plants or food made from animals eggs, meat, and dairy products as they feed on the plants.…”
Section: Bacillus As Biopesticides Biofertilizers and Bioinoculantsmentioning
confidence: 99%
“…B. cereus is mesophilic, and is capable of adapting to wide and varying environmental conditions, widely distributed in nature and commonly found in nature as a saprophyte. It grows optimally at temperatures between 20 and 40 Vilain et al, 2006 . Since it is a soil bacterium, it can easily enter different food plants or food made from animals eggs, meat, and dairy products as they feed on the plants.…”
Section: Bacillus As Biopesticides Biofertilizers and Bioinoculantsmentioning
confidence: 99%
“…It was very difficult to break these clumps except through ultrasonication. Some Bacillus species were reported to revert to spore formation, only germinating and becoming active once the external environment was conducive for growth (Villain et al, 2006). The spore formation state was not observed with B. mycoides B16 through the malachite test.…”
Section: Ultrastructural Changes In Microcystis Cells During Lysis Afmentioning
confidence: 96%
“…The bacteria surrounding to the Microcystis, presumably also released extracellular substances that interfered with the Microcystis photosynthesis system as indicated by the collapse in the plasmalemma and thylakoid membranes that was more evident after 24 h of bacteria treatment (Figures 4.10b and f). Burnham et al (1984) and Daft et al (1985) showed that Myxococcus fulvus BG02 exhibited polymorphism: spherules and myxospores, which showed lytic activity against B. mycoides B16 switched from single cell to a multicellularity phenotypes which is a characteristics of rhizodal phenotypes of B. mycoides species (Villain et al, 2006). The rhizoidal growth of B. mycoides through chain elongation over long distance may be viewed as translocation through the Microcystis algal blooms.…”
Section: Ultrastructural Changes In Microcystis Cells During Lysis Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus cereus is a facultatively anaerobic, spore-forming, opportunistic human pathogen (25,56). The majority of reported illnesses involving B. cereus are food-borne intoxications, classified as emetic and diarrheal syndromes (28,48).…”
mentioning
confidence: 99%